Evaluación del estado de las heridas en terneros tras la aplicación de diferentes métodos de castración - Pared, Valeria E.; Jara, M.L.; Pereira, Maria Mercedes; Chavez, A.; Romero, A.; Gandara, Luis; Sussini, Paolo Adrián; Maldonado Vargas, Pablo; Aguilar, Natalia M. Alejandra (Facultad de Ciencias Veterinarias, Universidad Nacional del Nordeste, 2025)
Poster